2008
DOI: 10.1530/rep-07-0314
|View full text |Cite
|
Sign up to set email alerts
|

The onset of puberty in female mice as reflected in urinary steroids and uterine/ovarian mass: interactions of exposure to males, phyto-oestrogen content of diet, and ano-genital distance

Abstract: Development of puberty in female mice was examined in relationship with the ano-genital distance index (AGDI), phyto-oestrogen content of diet and exposure to males post weaning. Throughout gestation and post-natal development, females were exposed to a regular diet or a nutritionally similar diet deficient in phyto-oestrogens. After segregation at weaning on the basis of short or long AGDI, an indirect measure of in utero androgen exposure, females were housed alone or underneath two outbred adult males for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
(66 reference statements)
2
8
0
Order By: Relevance
“…There appears to be a strong relationship between urine progesterone and PDG, suggesting a relatively simple, though crude, transformation that links the 2 values (Stanczyk et al 1997, Falk et al 1999. The urine progesterone values were similar to other mammals (Herrick et al 2000, Khan et al 2008) and comparable to the transformed PDG values reported in other cetaceans (Robeck et al 2004(Robeck et al , 2005. Urine data was available for only 2 demographic groups in the present study: immature males and immature females.…”
Section: Urine Progesteronesupporting
confidence: 86%
“…There appears to be a strong relationship between urine progesterone and PDG, suggesting a relatively simple, though crude, transformation that links the 2 values (Stanczyk et al 1997, Falk et al 1999. The urine progesterone values were similar to other mammals (Herrick et al 2000, Khan et al 2008) and comparable to the transformed PDG values reported in other cetaceans (Robeck et al 2004(Robeck et al , 2005. Urine data was available for only 2 demographic groups in the present study: immature males and immature females.…”
Section: Urine Progesteronesupporting
confidence: 86%
“…This suggests that weight is a poor indicator of age. Furthermore, housing males in close proximity to females can accelerate the onset of female puberty (Khan et al 2008; Vandenbergh 1967; Vandenbergh et al 1976). Overall, there are many social and environmental determinants of the highly variable onset of puberty.…”
Section: Adolescence and Relevant Maturationmentioning
confidence: 99%
“…However, other evidence has shown that a male's preputial glands are not necessary for his ability to induce growth of the female's uterus and ovaries ). It is likely that there are convergent mechanisms that may each be sufficient and that multiple triggers are involved in various physiological and behavioural measures of female reproductive maturation (Vandenbergh 1967, Bronson & Desjardins 1974, Khan et al 2008a. Our data implicating male urinary E 2 in the Vandenbergh effect are specific to measures of uterine growth, and further research would be necessary to generalise our hypothesised mechanism to other measures of reproductive maturity.…”
Section: Discussionmentioning
confidence: 74%
“…This phyto-oestrogen-free diet contains !10.0 ppm total isoflavones (aglycone equivalents of genistein, daidzein and glycitein). Ingredients of the two diets are previously described (Khan et al 2008a). After at least 2 months on their respective diets, males were exposed to juvenile females and recently inseminated females in the exposure apparatus using protocols described below.…”
Section: Comparison Of Males On Soy-based and Phyto-oestrogenfree Dietsmentioning
confidence: 99%
See 1 more Smart Citation